PERHITUNGAN ELEMEN MESIN DAN KAPASITAS PRODUKSI PADA MESIN PENCETAK MAKARONI BERTENAGA MOTOR LISTRIK - Suwarto; Imam; Suparno (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Technological developments are used to increase income as well as convenience in the world of production to increase economic income. Technology needs to be directed at all lines of life, one of which is the use of wheat flour. Using wheat flour can be made into macaroni which can be used as a food source and can also be used as a business idea. Processed wheat flour in the form of macaroni can be used as a source of carbohydrates which people enjoy. This macaroni printing machine with an automatic cutting system is a machine that is capable of printing macaroni, the way it works is changing the power and rotation of the driving electric motor into power and rotation on the screw extruder shaft with the knife shaft next to the tip. This machine is capable of making elbow-shaped macaroni. The hope is that this machine can be a solution for macaroni makers, especially for SMEs who specialize in selling snacks. From the results of the calculation of machine elements and capacity, the tool work process operates well. After designing the macaroni tool using a V belt type A32 using 2 pulleys with a diameter of 3 inches and 5 inches and the type of shaft material used is SS 304